Achieving reconstruction objectives within appropriate regulatory frameworks - Rotimi, J.O.B. (Australasian Universities Building Educators Association (AUBEA), 2006)
The paper describes an on-going research that explores improvement schemes on the regulatory framework that will facilitate the implementation of reconstruction after disasters in New Zealand. There is evidence suggesting that the existing regulatory provisions may cause procedural constraints, loss of pragmatism on the part of disaster practitioners, improper coordination arrangements coupled with unclear inter-agency responsibilities, which may eventually hinder the achievement of effective reconstruction programmes. The research focus and methodology are presented, to give an insight into the opportunities for research that will proffer best practice guidelines for achieving reconstruction objectives through appropriate regulatory frameworks.
Keywords: Legislation; Reconstruction